Macrocyclic naphthalene diimides as G-quadruplex binders. Issue 13 (1st July 2015) - Marchetti, Chiara; Minarini, Anna; Tumiatti, Vincenzo; Moraca, Federica; Parrotta, Lucia; Alcaro, Stefano; Rigo, Riccardo; Sissi, Claudia; Gunaratnam, Mekala; Ohnmacht, Stephan A.; Neidle, Stephen; Milelli, Andrea
Graphical abstract: Abstract: The synthesis, biological and molecular modeling evaluation of a series of macrocyclic naphthalene diimides is reported. The present investigation expands on the study of structure–activity relationships of prototype compound2 by constraining the molecule into a macrocyclic structure with the aim of improving its G-quadruplex binding activity and selectivity. The new derivatives, compounds4 –7 carry spermidine- and spermine-like linkers while in compound8 the inner basic nitrogen atoms of spermine have been replaced with oxygen atoms. The design strategy has led to potent compounds stabilizing both human telomeric (F21T) and c-KIT2 quadruplex sequences, and high selectivity for quadruplex in comparison to duplex DNA. Antiproliferative effects of the new derivatives4 –8 have been evaluated in a panel of cancer cell lines and all the tested compounds showed activity in the low micromolar or sub-micromolar range of concentrations. In order to rationalize the molecular basis of the DNA G-quadruplex versus duplex recognition preference, docking and molecular dynamics studies have been performed. The computational results support the observation that the main driving force in the recognition is due to electrostatic factors.